2021
DOI: 10.3389/fnins.2020.580762
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Extracorporeal Shock Wave Therapy on Spastic Muscle of the Wrist Joint in Stroke Survivors: Evidence From Neuromechanical Analysis

Abstract: Background: This study combined neuromechanical modeling analysis, muscle tone measurement from mechanical indentation and electrical impedance myography to assess the neural and peripheral contribution to spasticity post stroke at wrist joint. It also investigated the training effects and explored the underlying mechanism of radial extracorporeal shock wave (rESW) on spasticity.Methods: People with first occurrence of stroke were randomly allocated to rESW intervention or control group. The intervention group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 68 publications
(104 reference statements)
4
29
0
Order By: Relevance
“…This provides some insight that the mechanical properties may continue to deteriorate for an extended period of time postinjury, possibly due to muscle atrophy. Previous studies reported that the freq measurement of myotonometer was related to the MAS score in stroke survivors ( 35 ). This study did not observe a significant correlation between the MAS score and myotonometer.…”
Section: Discussionmentioning
confidence: 99%
“…This provides some insight that the mechanical properties may continue to deteriorate for an extended period of time postinjury, possibly due to muscle atrophy. Previous studies reported that the freq measurement of myotonometer was related to the MAS score in stroke survivors ( 35 ). This study did not observe a significant correlation between the MAS score and myotonometer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ESWT can induce nitric oxides, which seem to play an important role in spasticity relieving mechanisms through involving in the formation of neuromuscular junction formation in the peripheral nervous system and in physiological functions of the central nervous system ( 15 , 59 ). A new study by Leng et al ( 64 ) applied passive torque measurement combined with biomechanical modeling, myotonometer measurements, and electrical impedance myography to assess the changes of muscle properties induced by ESW in the spastic wrist joint, then concluded that both the neural and peripheral components played a role in muscle spasticity, and ESWT may be more effective in addressing the peripheral component of spasticity muscle.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies with electrophysiological measures did not report a significant difference in spastic muscle after ESWT treatment [21,22], suggesting that neuronal effects may not be the primarily mechanism of ESWT on spasticity [21].…”
Section: Reducing Motor Neuron Excitabilitymentioning
confidence: 99%
“…The mechanism of ESWT made a neural and peripheral contribution to muscle spasticity [21]. A peripheral effect, also known as a non-neural effect, was recognized through its effects on the rheological properties and fibrosis of chronic hypertonic muscles.…”
Section: Affecting Rheological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation